Grinding material slurry and grinding method thereof

By using manganese oxide particles, permanganate ions, phosphoric acids and water-soluble organic polymers in the abrasive material slurry, the problem of insufficient dispersion of existing abrasive material slurry is solved, and the effect of efficient grinding and long-term application period is achieved.

CN119547183APending Publication Date: 2025-02-28MITSUI MINING & SMELTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047739.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2023-06-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The dispersion of existing abrasive materials is insufficient, resulting in easy clogging and difficulty in washing during the grinding process, and the application period is short.

Method used

Abrasive material slurry containing manganese oxide particles, permanganate ions, phosphoric acids and water-soluble organic polymers is used to improve dispersion and grinding efficiency through the combination of these components.

Benefits of technology

It achieves excellent dispersion, high grinding rate and long application period, and reduces the use of washing water and washing time, and reduces the environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005192468660000011
    Figure HDA0005192468660000011
Patent Text Reader

Abstract

This polishing material slurry comprises: manganese oxide abrasive grains containing manganese oxide particles; permanganate ions; a phosphoric acid; and a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylate salts, salts of naphthalene sulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, and copolymers thereof. The method for polishing the polishing material slurry according to the present invention comprises polishing an object to be polished using the polishing material slurry according to the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to abrasive slurry and a grinding method thereof. Background Art

[0002] In the so-called power devices, semiconductor devices are used to replace the silicon used in the past as substrates by using silicon carbide (SiC), gallium nitride, diamond, etc. to achieve higher voltage resistance and higher current. Since the substrates formed by these materials have a larger band gap than the conventional silicon substrates, they can withstand higher voltages.

[0003] Among them, a substrate formed of silicon carbide (hereinafter referred to as a SiC substrate) is not only excellent in hardness, heat resistance, and scientific stability, but also excellent in terms of cost. On the other hand, since the SiC substrate has a higher hardness than the conventional silicon substrate, an abrasive slurry containing manganese oxide particles as abrasive grains, such as disclosed in Patent Document 1, has been developed as an abrasive slurry used in a polishing process such as a process of finishing the surface of the SiC substrate into a mirror surface in the manufacturing process of the SiC substrate and a polishing process using the so-called CMP (Chemical Mechanical Polishing) method.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-071787 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, most of the abrasive slurries containing manganese oxide particles as abrasive grains disclosed in Patent Document 1 have insufficient dispersibility, and the abrasive slurries are in a viscous liquid state, so the supply pipe for supplying the abrasive slurries is easily blocked. In addition, during the grinding process, since the abrasive slurry adheres to the surface of the SiC substrate as the object to be ground or the grinding pad used in the grinding, the abrasive slurry is difficult to fall off even when the grinding pad or SiC substrate after the grinding process is washed, and the washing process needs to spend time. Such abrasive slurries have a tendency to have a short pot life.

[0009] In view of the above problems, the present invention provides an abrasive slurry and a polishing method having excellent dispersibility, a high polishing rate, and a long pot life (also called usable time or workable time).

[0010] Means for solving problems

[0011] The grinding material slurry of the present invention, which is carried out to solve the above-mentioned problems, is characterized in that it has: manganese oxide abrasive particles containing manganese oxide particles; permanganate ions; phosphoric acids; and a polymer additive, which contains one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone and their copolymers.

[0012] The polishing material slurry of the present invention has manganese oxide abrasive particles containing manganese oxide particles, permanganate ions, phosphoric acid and a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone and their copolymers, so it has excellent dispersibility, shows a high polishing rate and has a long pot life.

[0013] In addition, the abrasive slurry of the present invention has excellent dispersibility, so it is easy to wash the SiC substrate or polishing pad as the object to be polished, the use amount of washing water can be suppressed, the washing time can be shortened, and the amount of wastewater treatment can be reduced, which can reduce the environmental load. Furthermore, the abrasive slurry of the present invention can shorten the polishing process time because it shows a high polishing rate.

[0014] Manganese oxide particles contained in the manganese oxide abrasive grains include manganese (II) oxide (MnO), dimanganese (III) trioxide (Mn2O3), manganese (IV) dioxide (MnO2), trimanganese (II, III) tetraoxide (Mn3O4), etc. It should be noted that the manganese oxide abrasive grains may be a mixture of one or more manganese oxide particles.

[0015] In addition, the manganese oxide abrasive grains may also contain abrasive grains other than the above-mentioned manganese oxide particles within the range that the effect of preventing the warping and cracking caused by the Twyman effect on the object to be polished, such as a SiC substrate, as the abrasive slurry of the present invention, is not damaged. As abrasive grains other than manganese oxide particles, compounds such as oxides, hydroxides, carbides, and other carbon materials of at least one element selected from Mg, B, Si, Ce, Al, Zr, Fe, Ti, and Cr can be listed. Specifically, aluminum oxide, silicon dioxide, cerium oxide, zirconium oxide, titanium oxide, chromium oxide, iron oxide, magnesium hydroxide, cerium hydroxide, silicon carbide, boron carbide, and diamond can be listed. They can also be used in one or in combination of two or more. In addition, the manganese oxide particles can also be composited with abrasive grains other than manganese oxide particles, for example, particles obtained by surface coating of manganese oxide particles by abrasive grains other than manganese oxide particles, or particles obtained by covering the surface of abrasive grains other than manganese oxide particles by manganese oxide particles.

[0016] In addition, if the cumulative volume 50% particle size (D50) of the manganese oxide abrasive grains obtained by laser diffraction / scattering particle size distribution measurement is 0.1 μm or more, it is preferred from the viewpoint of having a high polishing force, and if it is 5.0 μm or less, it is preferred from the viewpoint of suppressing the roughness of the surface of the object to be polished, such as a SiC substrate. Therefore, the cumulative volume 50% particle size (D50) of the manganese oxide abrasive grains obtained by laser diffraction / scattering particle size distribution measurement is more preferably 0.15 μm or more and 4.5 μm or less, and further preferably 0.2 μm or more and 4.0 μm or less.

[0017] Here, the particle size (D50) of the manganese oxide abrasive grains at a cumulative volume of 50% obtained by the laser diffraction / scattering particle size distribution measurement method is prepared by diluting a mixture obtained by bead-crushing the manganese oxide abrasive grains in the method for manufacturing the abrasive slurry of the present invention described later with water so that the concentration of the mixture becomes about 0.01%, and then measuring it using a laser diffraction / scattering particle size distribution measurement device (MicrotracBEL Co., Ltd.: MT3300EXII).

[0018] Furthermore, from the viewpoint of fully improving the grinding rate of high hardness materials such as silicon carbide, ensuring the preferred fluidity of the abrasive in the grinding slurry, and preventing the viewpoint of agglomeration, the content of the manganese oxide abrasive contained in the grinding material slurry of the present invention is preferably 0.5 mass % or more and 20 mass % or less, and more preferably 0.5 mass % or more and 10 mass % or less relative to the total amount of the grinding slurry. In addition, if the content of the manganese oxide particles contained in the manganese oxide abrasive is 1 mass % or more and 5 mass % or less, it is further preferred from the viewpoint of fully improving the grinding rate. It should be noted that in this specification, the content in the grinding material slurry of the present invention is the content in the grinding slurry before the start of grinding unless otherwise specified.

[0019] Furthermore, the polishing material slurry of the present invention contains permanganate ions (MnO4 - ). The permanganate ions can have a high grinding force on high hardness materials such as silicon carbide by being used in combination with manganese oxide abrasive grains as an oxidant. Here, the supply source of the permanganate ions is preferably permanganate. The permanganate may include alkali metal salts of permanganate or alkaline earth metal salts of permanganate. Furthermore, from the perspective of easy acquisition and improvement of the grinding efficiency of the abrasive slurry of the present invention, the permanganate as the supply source of the permanganate ions is preferably an alkali metal salt of permanganate, and more preferably sodium permanganate or potassium permanganate. It should be noted that these permanganates may be used alone or in combination of two or more.

[0020] In addition, from the viewpoint of fully improving the grinding rate, the content of the permanganate ion in the grinding material slurry of the present invention is preferably 0.5 mass % or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the viewpoint of preventing the crystallization caused by increasing the addition, ensuring the safety of the operation of the grinding material slurry, or even if the addition is increased, the tendency of the grinding rate saturation will occur, etc., the content of the permanganate ion in the grinding material slurry of the present invention is preferably 3.2 mass % or less relative to the total amount of the grinding material slurry of the present invention. That is, the content of the permanganate ion is preferably 0.5 mass % or more and 3.2 mass % or less relative to the total amount of the grinding material slurry of the present invention, more preferably 1.0 mass % or more and 2.1 mass % or less. It should be noted that the content of the permanganate ion is measured by ion chromatography or absorptiometry.

[0021] Furthermore, the polishing material slurry of the present invention contains phosphoric acid in addition to the above-mentioned manganese oxide abrasive and permanganate ions. Phosphoric acid can improve the dispersibility of the polishing material slurry of the present invention by using it together with manganese oxide abrasive and permanganate ions.

[0022] The phosphoric acid contained in the polishing material slurry of the present invention is preferably an inorganic phosphorus compound. Specifically, as the phosphoric acid compound, sodium phosphate (trisodium phosphate (anhydride) (Na3PO4), CAS number: 7601-54-9; trisodium phosphate 12 hydrate (Na3PO4·12H2O), CAS number: 10101-89-0; sodium dihydrogen phosphate (NaH2PO4), CAS number: 7558-80-7; disodium hydrogen phosphate (Na2HPO4), CAS number: 7558-79-4) or potassium phosphate (tripotassium phosphate) can be listed. (anhydride) (K3PO4), CAS number: 7778-53-2; tripotassium phosphate monohydrate (K3PO4·H2O), CAS number: 27176-10-9; dipotassium hydrogen phosphate trihydrate (K2HPO4·H2O), CAS number: 16788-57-1; monopotassium dihydrogen phosphate (KH2PO4), CAS number: 7778-77-0; dipotassium hydrogen phosphate (K2HPO4), CAS number: 7758-11-4).

[0023] In addition, as the metaphosphate compound, sodium metaphosphate (NaPO3) can be cited. n , CAS No.: 35270-09-8) or potassium metaphosphate (KPO3) n ,CAS number: 7790-53-6.

[0024] Examples of the hexametaphosphate compound include sodium hexametaphosphate (NaH7P6O 18 ), CAS number: 10124-56-8.

[0025] Examples of the pyrophosphate compound include sodium pyrophosphate (sodium pyrophosphate (anhydrous) (Na4P2O7), CAS number: 7722-88-5; sodium pyrophosphate decahydrate (Na4P2O7·10H2O), CAS number: 13472-36-1; acidic sodium pyrophosphate (Na2H2P2O7), CAS number: 7758-16-9) or potassium pyrophosphate (K4P2O7), CAS number: 7320-34-5.

[0026] Examples of polyphosphate compounds include sodium polyphosphate (Na3P3O 10 X2), CAS number: 68915-31-1; potassium polyphosphate (K3P3O 10 X2), CAS number: 68956-75-2.

[0027] Examples of tripolyphosphate compounds include sodium tripolyphosphate (Na5P3O 10 ), CAS number: 7758-29-4 or potassium tripolyphosphate (K5P3O 10 ), CAS number: 13845-36-8.

[0028] Furthermore, their salts or hydrates can be listed. In the case of their salts, preferably alkali metal salts or alkaline earth metal salts, particularly more preferably sodium salts or potassium salts. In addition, particularly in the grinding material slurry of the present invention, from the viewpoint of a small amount of effective high dispersibility and the viewpoint of fully improving the grinding rate, more preferably metaphosphate compounds, hexametaphosphate compounds, pyrophosphate compounds (sodium pyrophosphate, potassium pyrophosphate), polyphosphate compounds (sodium polyphosphate or potassium polyphosphate) or tripolyphosphate compounds. It should be noted that these phosphoric acids can also be used one or two or more are mixed and used.

[0029] Furthermore, among the above-mentioned inorganic phosphorus compounds, pyrophosphate compounds are preferred from the viewpoint of high dispersibility and sufficient improvement of polishing rate. Among the pyrophosphate compounds, alkali metal salts of pyrophosphate and alkaline earth metal salts of pyrophosphate are more preferred, and sodium pyrophosphate or potassium pyrophosphate is particularly preferred.

[0030] In addition, from the viewpoint of dispersibility, the content of phosphoric acid in the grinding material slurry of the present invention is preferably 0.001% by mass or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the aspect that the tendency of saturation of the grinding rate will occur even if the addition amount is increased, the content of phosphoric acid in the grinding material slurry of the present invention is preferably 0.1% by mass or less relative to the total amount of the grinding material slurry of the present invention. That is, the content of phosphoric acid is preferably 0.001% by mass or more and 0.1% by mass or less relative to the total amount of the grinding material slurry of the present invention, and is more preferably 0.002% by mass or more from the viewpoint of improving dispersibility, and is more preferably 0.05% by mass or less from the viewpoint of fully improving the grinding rate. It should be noted that in this specification, the content of phosphoric acid is the total amount of the compound classified as phosphoric acid as long as there is no special description.

[0031] Furthermore, if the content of phosphoric acid in the abrasive slurry of the present invention is expressed as a mass ratio relative to the content of manganese oxide abrasive in the abrasive slurry of the present invention, it is preferably 0.05% to 5.0%, more preferably 0.07% to 3.0%, and even more preferably 0.1% to 2.0%.

[0032] In addition, the abrasive slurry of the present invention contains, in addition to the above-mentioned manganese oxide abrasive grains, permanganate ions, and phosphoric acid, a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, and copolymers thereof. By containing the above-mentioned polymer additive, the abrasive slurry of the present invention can extend the pot life.

[0033] Furthermore, the water-soluble organic polymer preferably has a number average molecular weight (Mn) of 1000 or more and 10000 or less, a weight average molecular weight (Mw) of 1000 or more and 1000000 or less, a z average molecular weight (Mz) of 5000 or more and 1000000 or less, a ratio of Mw to Mn, i.e., a dispersion (Mw / Mn) of 0.1 or more and 150 or less, and a ratio of Mz to Mw (Mz / Mw) of 0.1 or more and 20 or less. Here, the number average molecular weight (Mn) is more preferably 2000 or more and 8000 or less. Typically, the number average molecular weight (Mn) can also be 3000 or more and 6000 or less. The weight average molecular weight (Mw) is more preferably 3500 or more and 100000 or less, and further preferably 4000 or more and 50000 or less. Typically, the weight average molecular weight (Mw) may also be 5000 or more and 20000 or less. The z-average molecular weight (Mz) is more preferably 6000 or more and 100000 or less. Typically, the z-average molecular weight (Mz) may also be 6500 or more and 75000 or less, or 7000 or more and 50000 or less. The dispersity (Mw / Mn) is more preferably 0.5 or more and 75 or less, and more preferably 0.8 or more and 10 or less. Typically, the dispersity (Mw / Mn) may also be 0.9 or more and 5. The ratio of Mz to Mw (Mz / Mw) is more preferably 0.5 or more and 15 or less, and more preferably 0.8 or more and 10 or less. Typically, the ratio of Mz to Mw (Mz / Mw) may also be 0.9 or more and 5 or less. On the other hand, if CMC (carboxymethyl cellulose) is contained as a polymer additive, the application period of the abrasive slurry is short as described below.

[0034] Here, the number average molecular weight (Mn), weight average molecular weight (Mw) and z-average molecular weight (Mz) based on polyethylene glycol (PEG) conversion measured by GPC can be measured and analyzed according to the following conditions. In addition, the dispersion degree (Mw / Mn) and the ratio (Mz / Mw) of Mz to Mw are calculated from the obtained number average molecular weight (Mn), weight average molecular weight (Mw) and z-average molecular weight (Mz).

[0035] = Molecular weight determination conditions =

[0036] Measuring device: HPLC Prominence series (manufactured by Shimadzu Corporation)

[0037] Device composition: CBM20A, DGU-20A3R, LC-20AD, SIL-20ACHT, CTO-20AC, RID-10A

[0038] Column: Shodex OHpak SB-803HQ (manufactured by Resonac Co., Ltd.)

[0039] Temperature: 40℃

[0040] Flow rate: 1.0ml / min

[0041] Detector: Differential refractive index detector

[0042] Eluent: 0.1M sodium chloride aqueous solution

[0043] =Analysis software=

[0044] Software: LabSolutions / LCsolution GPC (manufactured by Shimadzu Corporation)

[0045] Version: 1.25SP2

[0046] Furthermore, in the case where the aqueous solution obtained by dissolving the above-mentioned water-soluble organic polymer in water is high viscosity, it is difficult to measure each molecular weight by the above-mentioned GPC. In this case, the viscosity of the aqueous solution of the water-soluble organic polymer set to 1% by mass at a liquid temperature of 25°C is preferably 10000mPa·s or more and 30000mPa·s or less. Typically, the viscosity may also be 11000mPa·s or more and 27000mPa·s or less, 12000mPa·s or more and 24000mPa·s or less, or 13000mPa·s or more and 21000mPa·s or less. It should be noted that the viscosity determination of the water-soluble organic polymer is set to be implemented using a digital rotational viscometer DV3T (manufactured by Eikon Seiki Co., Ltd.), and is set to a value obtained by measuring the condition of a rotation speed of 0.01rpm.

[0047] In addition, in the abrasive slurry of the present invention, the above-mentioned polymer additive is more preferably one or more water-soluble organic polymers selected from polycarboxylic acids, polycarboxylates and their copolymers, and the above-mentioned polymer additive is further preferably one or more water-soluble organic polymers selected from polyacrylic acid, polymaleic acid, polyacrylate, polymaleate and their copolymers. The above-mentioned polymer additive is particularly preferably a polyacrylate, and the above-mentioned polymer additive is more particularly preferably an ammonium polyacrylate.

[0048] In addition, from the viewpoint of dispersibility, the content of the polymer additive in the grinding material slurry of the present invention is preferably 0.006 mass % or more relative to the total amount of the grinding material slurry of the present invention. In addition, from the viewpoint of fully improving the polishing rate, the content of the polymer additive in the grinding material slurry of the present invention is preferably 0.05 mass % or less relative to the total amount of the grinding material slurry of the present invention. That is, the content of the polymer additive is preferably 0.006 mass % or more and 0.05 mass % or less relative to the total amount of the grinding material slurry of the present invention, more preferably 0.01 mass % or more and 0.03 mass % or less. It should be noted that in this specification, the content of the polymer additive is the total amount of the compound classified as the above-mentioned polymer additive as long as there is no special description.

[0049] Furthermore, if the content of the polymer additive in the abrasive slurry of the present invention is expressed as a mass ratio relative to the content of the manganese oxide abrasive in the abrasive slurry of the present invention, it is preferably greater than 0.3% and less than 2.5%, more preferably greater than 0.4% and less than 2.0%, and further preferably greater than 0.5% and less than 1.0%.

[0050] In addition, the grinding material slurry of the present invention is characterized in that the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ion is greater than 0.5 mass% and less than 3.2 mass%, the content of the above-mentioned phosphoric acid is greater than 0.001 mass% and less than 0.1 mass%, and the content of the above-mentioned polymer additive is greater than 0.006 mass% and less than 0.05 mass%.

[0051] As described above, in the polishing material slurry of the present invention, if the content of the above-mentioned manganese oxide abrasive is greater than 0.5 mass% and less than 20 mass%, the content of the above-mentioned permanganate ion is greater than 0.5 mass% and less than 3.2 mass%, the content of the above-mentioned phosphoric acid is greater than 0.001 mass% and less than 0.1 mass%, and the content of the above-mentioned polymer additive is greater than 0.006 mass% and less than 0.05 mass%, it is preferred from the aspects of excellent dispersibility, high polishing rate and long applicability.

[0052] Here, the grinding material slurry of the present invention contains a dispersion medium for dissolving or dispersing the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid and polymer additives. If the dispersion medium is a water-soluble organic solvent such as water, alcohol or ketone or a mixture thereof, it is preferred in terms of fully improving the polishing rate, and water is more preferred. The content of the dispersion medium is preferably 60% by mass or more and 99.9% by mass or less relative to the total amount of the grinding material slurry, and more preferably 80% by mass or more and 90% by mass or less.

[0053] Furthermore, the grinding material slurry of the present invention may also contain any additives other than the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid, polymer additives and dispersion medium. Among them, the arbitrary additives are dispersants, pH adjusters, viscosity adjusters, chelating agents and rust inhibitors. The content of the arbitrary additives is preferably 40% by mass or less, more preferably 20% by mass or less, and further preferably 10% by mass or less relative to the total amount of the grinding material slurry of the present invention.

[0054] It should be noted that the abrasive slurry of the present invention can be set in a form in which the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acid, polymer additives, dispersion medium and any additives are appropriately mixed, for example, it can also be set in a set of preparations in which these components are divided into two or more kinds. The composition of the set can be any form as long as the grinding ability can be fully exerted when adjusting the abrasive slurry.

[0055] A polishing method for polishing an object to be polished using the above-mentioned abrasive slurry of the present invention will be described below.

[0056] The following polishing methods can be listed: supplying the abrasive slurry of the present invention to a polishing pad, making the polished surface of the object to be polished contact with the polishing pad, and polishing by relative movement between the two. Here, it can also be a method of allowing the abrasive slurry of the present invention to flow freely, or a method of circulating the abrasive slurry of the present invention by repeatedly performing the following operations: recovering the abrasive slurry of the present invention supplied to the polishing pad for polishing, and supplying the recovered abrasive slurry of the present invention to the polishing pad again. Since the abrasive slurry of the present invention can be circulated repeatedly to polish the object to be polished, the usage amount can be suppressed. Here, the polishing pad can use, for example, non-woven fabrics that have been used so far, or pads impregnated with resins such as polyurethane or epoxy, and suede materials. If the polishing pressure is 0.5×10 4 Pa or more and 1.0×10 5 Pa or less, especially 1.0×10 4 Pa or more and 5.0×10 4 Pa or less is preferred from the perspectives of polishing force and ease of operation of the polishing jig. The supply rate of the polishing material slurry is preferably 10 mL / min to 500 mL / min, more preferably 50 mL / min to 250 mL / min.

[0057] The object to be ground by the abrasive slurry of the present invention is, for example, a high-hardness material with a Mohs hardness of 8 or more. Here, the Mohs hardness is a result of a method of applying scars to a standard material and digitizing the hardness, and can be measured by a Mohs hardness meter by a conventional method. The Mohs hardness specifies standard materials ranging from 1 to 10 in order from softness, and the specific standard materials are: Mohs hardness 1 is talc, 2 is gypsum, 3 is calcite, 4 is fluorite, 5 is apatite, 6 is orthoclase, 7 is quartz, 8 is topaz, 9 is corundum, and 10 is diamond. Mohs hardness is a high-hardness material with a hardness of 8 or more on the Mohs hardness meter, for example, silicon carbide (Mohs hardness of about 9), gallium nitride (Mohs hardness of about 9), diamond, etc.

[0058] Moreover, the abrasive slurry of the present invention can be used for the CMP (Chemical Mechanical Polishing) process after the polishing of the substrate formed by the high hardness material. In particular, the abrasive slurry of the present invention can be used for the polishing of the substrate formed by silicon carbide (SiC), that is, the SiC substrate, which can fully improve the polishing rate and effectively prevent the warping and cracking caused by the Terwyman effect. SiC substrates usually use single-crystal silicon carbide substrates. As a result, as its crystal system, hexagonal crystals or rhombohedral crystals can usually be listed. From the perspective of the effect of the abrasive slurry that can prevent the warping and cracking caused by the Terwyman effect, hexagonal crystals are preferred. The polymorphs of hexagonal crystals are 2H, 4H, 6H, 8H, and 10H. The polymorphs of rhombohedral crystals are 15R.

[0059] Next, the method for producing the abrasive slurry of the present invention described above will be described below.

[0060] First, pure water, manganese dioxide (abrasive, MnO2), phosphoric acid (for example, sodium salt of pyrophosphate), a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone and their copolymers, and beads (made of zirconium oxide, φ0.4 mm) are added to a container, and the container is placed on a paint shaker (60 Hz) and rotated at high speed to mix and grind the manganese dioxide (abrasive, MnO2).

[0061] The mixture containing the mixed and pulverized manganese dioxide (abrasive grains, MnO 2 ) in the container is separated from the beads using a centrifugal separator (himac CT 6E manufactured by Hitachi Koki Co., Ltd.), and the supernatant is collected.

[0062] The solid content concentration in the collected supernatant, that is, the manganese oxide abrasive concentration, was measured with a heated moisture meter, and pure water was added so as to achieve a predetermined concentration, thereby obtaining an abrasive slurry intermediate.

[0063] Then, the abrasive slurry of the present invention is obtained by mixing the abrasive slurry intermediate with potassium permanganate (KMnO 4 ).

[0064] It should be noted that, in the present specification, when “X to Y” (X, Y are arbitrary numbers) is expressed, unless otherwise specified, it includes the meaning of “X or more and Y or less”, and also includes the meaning of “preferably greater than X” or “preferably less than Y”. In addition, when it is expressed as “X or more” (X is an arbitrary number) or “Y or less” (Y is an arbitrary number), it also includes the intention of “preferably greater than X” or “preferably less than Y”.

[0065] Effects of the Invention

[0066] The abrasive slurry of the present invention has excellent dispersibility, can sufficiently increase the polishing rate, and has a long pot life. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a table showing the physical property values ​​and measurement results of the polishing slurries of Examples 1 to 9 and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0068] Hereinafter, the polishing material slurry according to the embodiment of the present invention will be further described by the following examples. However, the following examples do not limit the present invention.

[0069] (Example 1)

[0070] Pure water, manganese dioxide (MnO2) as abrasive, sodium pyrophosphate as phosphoric acid (specifically, sodium pyrophosphate·10hydrate (Na4P2O7·10H2O), CAS No.: 13472-36-1), ammonium polyacrylate as a polymer additive (number average molecular weight (Mn): 5500, weight average molecular weight (Mw): 7500, z average molecular weight (Mz): 9200, dispersion degree (Mw / Mn): 1.4, ratio of Mz to Mw (Mz / Mw): 1.2), and beads (made of zirconium oxide, φ0.4 mm) are added to a container, and the container is placed on a paint shaker (60 Hz) and rotated at high speed to mix and grind the manganese dioxide. The contents of these components were prepared so that the content of manganese dioxide was 30 mass %, the content of sodium pyrophosphate was 0.03 mass %, and the content of ammonium polyacrylate was 0.01 mass % based on the total amount of the abrasive slurry of Example 1.

[0071] The mixture containing the mixed and pulverized manganese dioxide in the container is separated from the beads using a centrifugal separator (himac CT 6E manufactured by Hitachi Koki Co., Ltd.) or the like, and the supernatant is collected. The supernatant obtained in this step becomes a measurement sample before the addition of potassium permanganate in the dispersibility test described later.

[0072] The solid content concentration in the collected supernatant, that is, the manganese oxide abrasive concentration, was measured with a heated moisture meter, and pure water was added so as to achieve a predetermined concentration, thereby obtaining an abrasive slurry intermediate.

[0073] Then, the abrasive slurry of Example 1 is obtained by mixing the abrasive slurry intermediate with an aqueous solution of potassium permanganate (KMnO4) having a KMnO4 mass% concentration of 3.2 mass%. The content of permanganate ions is prepared in such a way that it becomes 1.2 mass% relative to the total amount of the abrasive slurry of Example 1. In addition, the mass ratio of the total content of phosphoric acids in Example 1 to the content of manganese oxide abrasive is 0.10%. In addition, the mass ratio of the total content of polymer additives in Example 1 to the content of manganese oxide abrasive is 0.50%. It should be noted that the abrasive slurry of Example 1 obtained in this process becomes the measurement sample after the addition of potassium permanganate in the dispersibility test described later. In addition, Figure 1 The composition of the abrasive slurry shown in is the composition of the final product.

[0074] (Example 2)

[0075] In Example 2, the same manufacturing method as in Example 1 was carried out except that the content of manganese dioxide was 0.5% by mass relative to the total amount of the abrasive slurry of Example 2, thereby obtaining the abrasive slurry of Example 2. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 2 was 0.40%. In addition, the mass ratio of the total content of polymer additives to the content of manganese oxide abrasive grains in Example 2 was 2.00%.

[0076] (Example 3)

[0077] In Example 3, the abrasive slurry intermediate was mixed with a potassium permanganate (KMnO4) aqueous solution having a KMnO4 mass% concentration of 5.6 mass% to prepare the abrasive slurry in Example 3 in such a manner that the content of permanganate ions was 3.2 mass% relative to the total amount of the abrasive slurry in Example 3. The abrasive slurry in Example 3 was obtained by the same manufacturing method as in Example 1. It should be noted that the mass ratio of the total content of phosphoric acid in Example 3 to the content of manganese oxide abrasive grains was 0.10%. In addition, the mass ratio of the total content of polymer additives in Example 3 to the content of manganese oxide abrasive grains was 0.50%.

[0078] (Example 4)

[0079] In Example 4, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was 0.001 mass % relative to the total amount of the abrasive slurry of Example 4, thereby obtaining the abrasive slurry of Example 4. It should be noted that the mass ratio of the total content of phosphoric acid relative to the content of manganese oxide abrasive grains in Example 4 was 0.05%. In addition, the mass ratio of the total content of polymer additives in Example 4 relative to the content of manganese oxide abrasive grains was 0.50%.

[0080] (Example 5)

[0081] In Example 5, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was 0.1% by mass relative to the total amount of the abrasive slurry of Example 5, thereby obtaining the abrasive slurry of Example 5. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Example 5 was 5.00%. In addition, the mass ratio of the total content of polymer additives to the content of manganese oxide abrasive grains in Example 5 was 0.50%.

[0082] (Example 6)

[0083] In Example 6, the content of sodium pyrophosphate is 0.0018 mass % relative to the total amount of the polishing material slurry of Example 6, and other phosphoric acids (specifically, tripotassium phosphate (anhydride) (K3PO4), CAS No.: 7778-53-2, sodium metaphosphate (NaPO3) n , CAS No.: 35270-09-8, Potassium pyrophosphate (K4P2O7), CAS No.: 7320-34-5, Sodium polyphosphate (Na3P3O 10 X2), CAS No.: 68915-31-1 and sodium tripolyphosphate (Na5P3O 10 ), CAS No.: 7758-29-4, and the like) were mixed in equal amounts to obtain an abrasive slurry of Example 6. The same manufacturing method as in Example 1 was used except that the content of each of the above-mentioned samples was 0.0002% by mass. The abrasive slurry of Example 6 was obtained by the same manufacturing method as in Example 1. It should be noted that the mass ratio of the total content of phosphoric acid in Example 6 to the content of manganese oxide abrasive was 0.10%. In addition, the mass ratio of the total content of polymer additives in Example 6 to the content of manganese oxide abrasive was 0.50%.

[0084] (Example 7)

[0085] In Example 7, the content of ammonium polyacrylate was 0.009 mass % and the content of polyvinyl pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: polyvinyl pyrrolidone K25) (number average molecular weight (Mn): 4100, weight average molecular weight (Mw): 14000, z average molecular weight (Mz): 46000, degree of dispersion (Mw / Mn): 3.4, ratio of Mz to Mw (Mz / Mw): 3.3) was 0.001 mass % were prepared in the same manufacturing method as in Example 1, and the abrasive slurry of Example 7 was obtained. It should be noted that the mass ratio of the total content of phosphoric acid in Example 7 to the content of manganese oxide abrasive was 0.10%. In addition, the mass ratio of the total content of polymer additives in Example 7 to the content of manganese oxide abrasive was 0.50%.

[0086] (Example 8)

[0087] In Example 8, the same manufacturing method as in Example 1 was carried out except that the content of the ammonium polyacrylate was 0.006 mass % relative to the total amount of the abrasive slurry of Example 8, thereby obtaining the abrasive slurry of Example 8. It should be noted that the mass ratio of the total content of phosphoric acid compounds relative to the content of manganese oxide abrasive grains in Example 8 was 0.10%. In addition, the mass ratio of the total content of the polymer additives in Example 8 relative to the content of manganese oxide abrasive grains was 0.30%.

[0088] (Example 9)

[0089] In Example 9, the same manufacturing method as in Example 1 was carried out except that the content of the ammonium polyacrylate was 0.05% by mass relative to the total amount of the abrasive slurry of Example 9, thereby obtaining the abrasive slurry of Example 9. It should be noted that the mass ratio of the total content of phosphoric acid compounds relative to the content of manganese oxide abrasive grains in Example 9 was 0.10%. In addition, the mass ratio of the total content of the polymer additives in Example 9 relative to the content of manganese oxide abrasive grains was 2.50%.

[0090] (Comparative Example 1)

[0091] In Comparative Example 1, the same manufacturing method as in Example 1 was carried out except that no phosphoric acid and polymer additive were added, thereby obtaining the polishing material slurry of Comparative Example 1.

[0092] (Comparative Example 2)

[0093] In Comparative Example 2, the same manufacturing method as in Example 1 was carried out except that CMC (carboxymethyl cellulose) (number average molecular weight (Mn): 12400, weight average molecular weight (Mw): 2400000, z average molecular weight (Mz): 65000000, degree of dispersion (Mw / Mn): 193.5, ratio of Mz to Mw (Mz / Mw): 27.1) was prepared so as to be 0.25% by mass relative to the total amount of the abrasive slurry of Comparative Example 2 instead of the ammonium polyacrylate used in Example 1. The abrasive slurry of Comparative Example 2 was obtained. It should be noted that the mass ratio of the total content of phosphoric acid in Comparative Example 2 to the content of manganese oxide abrasive grains was 0.10%. In addition, the mass ratio of the total content of polymer additives in Comparative Example 2 to the content of manganese oxide abrasive grains was 12.5%.

[0094] (Comparative Example 3)

[0095] In Comparative Example 3, instead of manganese dioxide (MnO2) used in Example 1, silicon dioxide (SiO2) was prepared in such a manner that the amount was 2% by mass relative to the total amount of the abrasive slurry of Comparative Example 3; and potassium permanganate (KMnO4) was not added to the abrasive slurry intermediate. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry of Comparative Example 3. It should be noted that the mass ratio of the total content of phosphoric acid in Comparative Example 3 to the content of silicon oxide abrasive grains was 0.10%. In addition, the mass ratio of the total content of polymer additives in Comparative Example 3 to the content of silicon oxide abrasive grains was 0.50%.

[0096] (Comparative Example 4)

[0097] In Comparative Example 4, the same manufacturing method as in Example 1 was carried out except that the content of sodium pyrophosphate was 0.5% by mass relative to the total amount of the abrasive slurry of Comparative Example 4, thereby obtaining the abrasive slurry of Comparative Example 4. It should be noted that the mass ratio of the total content of phosphoric acid to the content of manganese oxide abrasive grains in Comparative Example 4 was 25.0%. In addition, the mass ratio of the total content of polymer additives to the content of manganese oxide abrasive grains in Comparative Example 4 was 0.50%.

[0098] Then, the following physical property values ​​were measured for the polishing material slurries of Examples 1 to 9 and Comparative Examples 1 to 4. The measured physical property values ​​and the measuring methods of the physical property values ​​are shown below, and the measurement results are shown in Figure 1 middle.

[0099] <Particle size evaluation>

[0100] The mixture containing the abrasive grains mixed and pulverized in a paint shaker in the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 was diluted with water so that the concentration of the mixture became about 0.01%, and a sample for measurement was prepared. Then, the particle size (D50) at the cumulative fraction of 50% based on volume was measured using a laser diffraction / scattering particle size distribution measuring apparatus (MT3300EXII manufactured by MicrotracBEL Co., Ltd.).

[0101] <Dispersibility Evaluation>

[0102] The dispersibility of the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 2 and 4 was evaluated before and after the addition of potassium permanganate, which is a source of permanganate ions.

[0103] First, the dispersibility before the addition of potassium permanganate is evaluated as follows. The mixture containing the abrasive grains mixed and crushed by the paint shaker in the grinding material slurry of Examples 1 to 9 and Comparative Examples 1 to 2 and 4 is diluted with water in a manner such that the concentration of the mixture becomes about 0.01 mass %, and a sample for measurement is prepared. Then, a particle size distribution measuring device (MicrotracBEL Co., Ltd.: MT3300EXII) is used to measure the particle size (D50) of the cumulative fraction of 50% on a volume basis. If D50 is less than 0.6 μm, it is evaluated as "O (Good)", and if D50 exceeds 0.6 μm, it is evaluated as "× (Bad)".

[0104] Next, the dispersibility after potassium permanganate addition is evaluated as follows. The sample for measurement is prepared by diluting with water in a manner such that the concentration of the abrasive slurry of Examples 1 to 9 and Comparative Examples 1 to 2 and 4 is about 0.01% by mass. Then, a laser diffraction / scattering particle size distribution measuring device (MicrotracBEL Co., Ltd.: MT3300EXII) is used to measure the particle size (D50) of the cumulative fraction of 50% on a volume basis. If D50 is less than 0.6 μm, it is evaluated as "0 (Good)", and if D50 exceeds 0.6 μm, it is evaluated as "× (Bad)". It should be noted that the abrasive slurry of Comparative Example 3 is not evaluated for the above-mentioned dispersibility because potassium permanganate (KMnO4) is not added to its abrasive slurry intermediate.

[0105] <Adhesion Evaluation>

[0106] The adhesion of the abrasive slurry of Examples 1 to 9 and Comparative Examples 1 to 4 is determined by visually recognizing the adhesion state of each abrasive slurry on the container (wide-mouthed bottle IBOY 250ml manufactured by AS ONE) containing the sample used in the dispersibility evaluation after the above-mentioned potassium permanganate addition by the tester, and judging as follows. When the container containing the sample is turned over, if the sample is not attached to the container, it is evaluated as "00 (Very Good)", the situation where the sample is only attached to the bottom of the container is evaluated as "0 (Good)", and the situation where the sample is attached to the bottom and side of the container, or attached to the side, is evaluated as "× (Bad)". It should be noted that for the abrasive slurry of Comparative Example 3, the slurry without adding potassium permanganate (KMnO4) in its abrasive slurry intermediate is set as the sample.

[0107] <Grinding test>

[0108] The polishing rates of the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 were evaluated by the following steps. A 4H-SiC substrate having a diameter of 4 inches and a deviation angle of 4° after CMP processing was used as the polishing object. The polishing test was performed on the Si surface of the substrate. A single-sided grinder BC-15 manufactured by MAT was used as the polishing device. An IC1000 manufactured by NITTA DuPont was used as the polishing pad mounted on the platform. The rotation speed of the platform was set to 60 rpm, and the peripheral speed was set to 7,136 cm / min. In addition, the carrier rotation speed was set to 60 rpm, and the peripheral speed was set to 961 cm / min. Furthermore, the load during polishing was set to 2.8 psi (approximately 1.96×10 4 The polishing rate was calculated from the difference in mass of the substrate before and after polishing. If the polishing rate was 0.10 μm / h or more, it was evaluated as "O (Good)", and if the polishing rate was less than 0.10 μm / h, it was evaluated as "× (Bad)".

[0109] <Crystallization Test>

[0110] Prepare each sample of Examples 1 to 9 and Comparative Examples 1 to 4. Store each prepared sample in a refrigerator set at 10°C for 24 hours. Afterwards, take each sample out of the refrigerator, and use a heating moisture meter to determine the solid content concentration in each sample, i.e., the total value of the manganese oxide abrasive concentration and the potassium permanganate concentration. If the solid content concentration after storage is 90% or more of the maintenance rate of the solid content concentration before storage, it is evaluated as "0 (Good)", and if the solid content concentration after storage is lower than 90% of the maintenance rate of the solid content concentration before storage, it is evaluated as "× (Bad)".

[0111] <Application period evaluation>

[0112] The pot life of Examples 1 to 9 and Comparative Examples 1 to 4 was evaluated as follows. The abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 were left standing at room temperature (25°C) for 3 days. The MnO4 - Concentration and MnO4 in the abrasive slurry before standing for 3 days - Compare the concentrations and calculate the MnO4 - Then, if MnO4 - The concentration of MnO4 was relative to that before standing for 3 days. - If the concentration maintenance rate is 80% or more, it is evaluated as "O (Good)". If the MnO4 - The concentration of MnO4 was relative to that before standing for 3 days. - The concentration maintenance rate was lower than 80%, which was evaluated as "Bad". - The concentration was evaluated as follows. First, the abrasive slurry was centrifuged (4,000 rpm × 20 min) to allow the manganese oxide abrasive particles in the abrasive slurry to settle. Next, 1.0 g of the supernatant was taken and diluted with 109 g of pure water to prepare a diluted solution. Then, the MnO4 in the diluted solution was measured using a spectrophotometer (UH-4150 manufactured by Hitachi High-Tech Science Co., Ltd.). - The absorbance of MnO4 was calculated by the pre-made standard curve. - concentration.

[0113] like Figure 1 As shown in , the abrasive slurries of Examples 1 to 9 have excellent dispersibility because the particle size (D50) at the volume-based cumulative fraction of 50% in the particle size distribution obtained by the laser diffraction / scattering method before and after the addition of potassium permanganate, a source of permanganate ions, is less than 0.6 μm.

[0114] Regarding the abrasive slurries of Examples 1 to 6 and 9, the adhesion state of the abrasive slurries on the container containing the sample was checked when the container was turned over. As a result, the sample did not adhere to the container, and the adhesion was very good. In addition, regarding the abrasive slurries of Examples 7 and 8, the adhesion state of the abrasive slurries on the container when the container containing the sample was turned over was checked. As a result, the sample adhered only to the bottom of the container, and the adhesion was good.

[0115] The polishing rate of the polishing material slurry of Examples 1 to 9 was 0.10 μm / h or more, and thus showed a high polishing rate.

[0116] The abrasive slurries of Examples 1 to 9 were left at room temperature (25°C) for 3 days and then the MnO4 - The concentration maintenance rate is 80% or more, so the pot life can be extended.

[0117] The invention disclosed in this specification includes, in addition to the configurations of each invention or embodiment, configurations specified by changing these partial configurations to other configurations disclosed in this specification within the applicable scope, configurations specified by adding other configurations disclosed in this specification to these configurations, or configurations specified by deleting these partial configurations to the extent that partial effects can be obtained.

[0118] Industrial Applicability

[0119] The abrasive slurry of the present invention is suitable as an abrasive for an object to be ground formed of a high hardness material because of its excellent dispersibility, high polishing rate, and long pot life. In addition, the abrasive slurry of the present invention is excellent in dispersibility, so it is easy to wash the SiC substrate and polishing pad as the object to be ground, and can reduce the use of washing water, shorten the washing time, and reduce the amount of wastewater treatment. The abrasive slurry of the present invention can reduce the environmental load because it shows a high polishing rate.

Claims

1. An abrasive slurry, characterized in that: It has: manganese oxide abrasive grains comprising manganese oxide particles; Permanganate ion; Phosphoric acids; and A polymer additive comprising one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid formaldehyde condensates, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, and copolymers thereof.

2. The abrasive slurry according to claim 1, characterized in that: The polymer additive is one or more water-soluble organic polymers selected from polycarboxylic acids, polycarboxylates and copolymers thereof.

3. The abrasive slurry according to claim 2, characterized in that: The polymer additive is one or more water-soluble organic polymers selected from polyacrylic acid, polyacrylic acid salts and copolymers thereof.

4. The abrasive slurry according to claim 3, characterized in that: The polymer additive is ammonium polyacrylate.

5. The abrasive slurry according to claim 1, characterized in that: The phosphoric acid is a pyrophosphate compound.

6. The abrasive slurry according to any one of claims 1 to 5, characterized in that The content of the manganese oxide abrasive grains is 0.5 mass % or more and 20 mass % or less, The content of the permanganate ion is 0.5 mass % or more and 3.2 mass % or less, The content of the phosphoric acid is 0.001 mass % or more and 0.1 mass % or less, The content of the polymer additive is 0.006 mass % or more and 0.05 mass % or less.

7. A grinding method, characterized in that: It includes: An object to be polished is polished using the abrasive slurry according to any one of claims 1 to 5.

8. A grinding method, characterized in that: It includes: An object to be polished is polished using the abrasive slurry according to claim 6.

Citation Information

Patent Citations

  • Polishing material slurry and polishing method

    JP2017071787A